Management of Small-Sustainable Coastal and Island Areas Based on Collaborative Management (Case Study in Bima Regency, West Nusa Tenggara) - Haeril Haeril; Eko Priyo Purnomo (Journal of Local Government Issues (LOGOS), 2019)
Given the rare terrain of land resources, the primary targets of Indonesia's economic development will be based on coastal zones and small islands and their sources. If not supported by the implementation of appropriate management policies, it can reduce the ability of coastal and small island ecosystems in the provision of sustainable natural resources. This research was conducted in Bima regency of West Nusa Tenggara aims to find out collaborative management in the effort of sustainable management of natural resources of the coastal area and small islands. Data collection is done through observation, interview, and questionnaire distribution. Involve 100 respondents consisting of, Head of Marine and Fishery, Head of Environment Agency, Head of Tourism Office, Community Monitoring Group, Non-Governmental Organization, and Environmental Community, and coastal community of districts Sape, Bolo, Lambu, Langgudu, and Wera. The result showed the implementation of collaborative management in the management of natural resources of coastal areas and small islands in a district of Bima has not active conducted when viewed from the achievements and respondents assessment based on the index scale of 1 to 5 on the indicators of the collaborative implementation management and sustainable development goals. Where the average value of collaborative management is only 3.25 or with enough category, also so in the implementation of sustainable development goals found the average value of the index of 3.32 even with enough class. Keyword: Sustainable development, collaborative management, coastal area and small islands, Bima Regency West Nusa Tenggara.